Antifungal Potential of Sansevieria Trifasciata Infusion as a Cleaner for Dentures - Dewi, Tri Purnami; Nurlitasari, Dewi Farida; Putra, Bagus Eda Purnariyawan (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2025)
Introduction: Thermoplastic nylon is one of the alternative materials used for denture bases, in addition to acrylic resin. It offers good flexibility and aesthetics; however, its high water absorption makes it susceptible to microbial colonization. Sansevieria trifasciata is a herbal plant known for its antiseptic, antibacterial, and antifungal properties. Therefore, it has the potential to be developed as a natural denture cleanser. This study aims to determine the antifungal effect of a 40% S. trifasciata var. laurentii infusion on the growth of Candida albicans colonies on thermoplastic nylon denture base plates. Material And Methods: This in vitro experimental study used a post-test only control group design with four groups: one negative control (sterile distilled water) and three groups treated with 40% S. trifasciata infusion for 24, 48, and 72 hours. A Candida albicans suspension (1.5 × 10⁸ CFU/mL) was prepared using McFarland standard 0.5. Phytochemical screening was conducted to identify active compounds in the extract. Data were analyzed using One-Way ANOVA and LSD post hoc test (p < 0.05). Results and Discussions: Phytochemical analysis of the S. trifasciata var. laurentii extract indicated the presence of saponins, phenols, flavonoids, and alkaloids, all of which are known to exhibit antifungal activity. The descriptive analysis showed that the treatment group with 72-hour immersion had the lowest average colony count of C. albicans. Statistical analysis using One-Way ANOVA showed a significant difference among the groups (p = 0.001). LSD post hoc analysis revealed that all treatment groups differed significantly from the control group (p < 0.05). These results indicate that prolonged immersion in S. trifasciata var. laurentii infusion enhances its antifungal efficacy. The observed antifungal activity is likely related to the disruption of fungal cell membranes by the active compounds present in the extract. Conclusion: The 40% S. trifasciata var. laurentii infusion is effective in inhibiting the growth of C. albicans on thermoplastic nylon denture base plates. The most significant antifungal effect was observed with a 72-hour immersion duration.